First Language Phonological Acquisition on a Two-Year-Old Child - Rosmania Rima (Journal of Linguistics, Literacy, and Pedagogy, 2023)
This paper discusses mainly the development of the language phonological acquisition of a two-year-old child during the linguistic period, especially on vowels and the factors that influence phonology acquisition. This study looks at the following questions: 1) How does a two-year-old acquire vowels? 2) What factors influence a child's phonological acquisition? First language acquisition (FLA) is the process of mastering a first language by children. In the early stages of development, humans begin to acquire their mother tongue or first language, which usually occurs between mother and child, other family members can follow, and it is done orally in the family environment informally. This study employs a case study approach to qualitative research because it displays the research findings based on facts found in the speakers' everyday lives and the process of language acquisition in the phonological features of the subject. This was gained through observation and diary notes. According to the findings of this examination, the subject has learned the vowels [a], [u], [e], [I], and [o]. Child’s phonological components of language acquisition are impacted by environmental variables, shown by the amount of vocabulary he obtains from family members, caretakers and surroundings.